PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR KETERAMPILAN GERAK DASAR SEPAK BOLA PADA SISWA KELAS V SD NEGERI 1 PECANGAAN WETAN JEPARA - Olivia Dwi Cahyani; Mohamad Afrizal; Vesti3 Dwi Cahyaningrum (Jurnal Ilmiah Hospitality, 2020)
This research is quantitative research. In this research, the number of 5th grade Students of SD Negeri 1 Pecangaan Wetan are 23 students who are consisted of 10 boys and 13 girls by applying the inquiry learning model in soccer learning. Before this research, researcher used t-test to assess the first ability of 5th grade Students of SD Negeri 1 Pecangaan Wetan.Based on the calculations obtained in the second cycle, the results are found that the target reached where students are 20 students (87%) as categorized completed and 3 students (13%) were not yet completed, it can be concluded, there is an increase in the results of student learning before and after being given the inquiry learning model.The suggestion in this research is the learning needs a lot of fun atmosphere, so that the students do not feel bored. The inquiry learning model is an alternative way which can be applied by the teacher as learning material.